Lent with Saint Augustine - Turek, Waldemar (Book collections on Project MUSE., 2014)
'Late have I loved you, Beauty so ancient and so new, ' prayed Saint Augustine. He searched long and passionately so, moving through various philosophies like a lost sheep. In the end, however, he discovered that God is near, within himself, in the depths of his soul. Augustine's Confessions immortalized the path of his conversion, a humble and sincere testimony of a sinner who experienced unconditional love. In Lent with Saint Augustine, Waldemar Turek presents selected excerpts for each day of Lent from this pearl of spirituality and literature, while incorporating commentary that takes the cycle of liturgical readings into account. These reflections serve as a prayerful aid for living Lent spiritually, allowing the reader to better experience the sacred while returning to the sources of faith to celebrate the death and resurrection of Christ.